Answer:
x = 4 , y = -6 thus: D.) is the answer
Explanation:
Solve the following system:
{y = -x/4 - 5 | (equation 1)
y = 10 - 4 x | (equation 2)
Express the system in standard form:
{x/4 + y = -5 | (equation 1)
4 x + y = 10 | (equation 2)
Swap equation 1 with equation 2:
{4 x + y = 10 | (equation 1)
x/4 + y = -5 | (equation 2)
Subtract 1/16 × (equation 1) from equation 2:
{4 x + y = 10 | (equation 1)
0 x+(15 y)/16 = -45/8 | (equation 2)
Multiply equation 2 by 16/15:
{4 x + y = 10 | (equation 1)
0 x+y = -6 | (equation 2)
Subtract equation 2 from equation 1:
{4 x+0 y = 16 | (equation 1)
0 x+y = -6 | (equation 2)
Divide equation 1 by 4:
{x+0 y = 4 | (equation 1)
0 x+y = -6 | (equation 2)
Collect results:
Answer: {x = 4 , y = -6